2019
DOI: 10.1186/s43031-019-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary insights from instructor interviews reconciling “structure and function” in biology, biochemistry, and chemistry through the context of enzyme binding

Abstract: Structure and function is an essential crosscutting concept in undergraduate STEM education and appears in numerous disciplines and contexts from the introductory to advanced levels. This concept is exemplified by enzyme binding, a topic spanning biology, biochemistry, and chemistry. We interviewed 13 instructors with primary instructional appointments in these fields, focusing on how they think about and also teach structure and function in their courses. We focused on how they define the component terms, "st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The fact that students suggested the idea that chemistry and biology courses should emphasize and clarify the connections between structure, properties, and function and that it is critical to do so for a sustained understanding and use of the content makes this an important area of investigation. Research exploring students’ understandings of ideas about SPF relationships in the contexts of specific phenomena relevant to chemistry and biology is limited; , however, in a recent publication, Yoho et al found that faculty in chemistry, biology, and biochemistry all emphasized the importance of these relationships in each discipline but also the importance and challenges (via instructor opinions) of bridging the disciplines using these ideas …”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The fact that students suggested the idea that chemistry and biology courses should emphasize and clarify the connections between structure, properties, and function and that it is critical to do so for a sustained understanding and use of the content makes this an important area of investigation. Research exploring students’ understandings of ideas about SPF relationships in the contexts of specific phenomena relevant to chemistry and biology is limited; , however, in a recent publication, Yoho et al found that faculty in chemistry, biology, and biochemistry all emphasized the importance of these relationships in each discipline but also the importance and challenges (via instructor opinions) of bridging the disciplines using these ideas …”
Section: Background and Significancementioning
confidence: 99%
“…The fact that students suggested the idea that chemistry and biology courses should emphasize and clarify the connections between structure, properties, and function and that it is critical to do so for a sustained understanding and use of the content 26 SPF relationships in the contexts of specific phenomena relevant to chemistry and biology is limited; 10,14 however, in a recent publication, Yoho et al found that faculty in chemistry, biology, and biochemistry all emphasized the importance of these relationships in each discipline but also the importance and challenges (via instructor opinions) of bridging the disciplines using these ideas. 27 ■ PURPOSE OF THIS PAPER Given (1) our interest in students building connections via CMR between chemistry and biology, (2) the importance of context in activating resources and how this might impact students' explanations, and (3) a gap in the literature studying student responses across these disciplines, we investigated student engagement in CMR using a task centered around protein−ligand binding, a biological structure−function phenomenon that can be explained using chemical principles associated with structure and properties. This task, however, serves as just one part of a three-part activity.…”
Section: Structure Properties and Functionmentioning
confidence: 99%
“…For example, gene expression in bacteria is largely dependent upon binding interactions of certain macromolecules and DNA, but it would simply take too long to teach and understand gene expression at this level of detail. The practical value of these chemistry-related bioscience subjects has made them heavily integrated into other areas of biology, bioengineering, and biomedicine curricula. ,,, …”
Section: Mitt Groups Are Needed To Study Complex Authentic Problems W...mentioning
confidence: 99%
“…A notable barrier to MITT curriculum design is ensuring curricular coherence and integration, especially when there are disagreements between staff from different disciplines about the specific content and methodology of delivery . A potential solution to issues of curricular coherence and integration is to ensure interactions between academics during all stages of curriculum design with regular meetings with module leaders presenting module plans to ensure awareness of the curriculum structure (potentially including modules taught by a multidisciplinary team of academics talking about a particular phenomenon, e.g., enzyme binding as a cross-cutting example of structure and function in biology, biochemistry, and chemistry) . This broad awareness offers opportunities for constructive overlaps between modules, thereby ensuring the best eventual outcome for staff and students who may find it challenging to make a connection between their background knowledge and its relation to other topics, topic sequencing for students from different backgrounds, and effective communication in multidisciplinary teams …”
Section: Mitt Curriculum Development and Implementation Is A Challengementioning
confidence: 99%
See 1 more Smart Citation